2009
DOI: 10.1111/j.1755-053x.2009.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives Use, Information Asymmetry, and MNC Post‐Acquisition Performance

Abstract: "We utilize a sample of US acquiring firms that engaged in international M&As to document the effects of corporate derivatives use on post-M&A long-term performance. We find that derivatives users outperform nonusers. Furthermore, we find that acquirers with derivative policies that are more comprehensive and sophisticated outperform those with less comprehensive and sophisticated policies. They, in turn, outperform acquirers with no existing policies in place. Our results are consistent with the notion that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…Additionally, we construct composite indices of asymmetric information and uncertainty aggregating the aforementioned proxies (Lin et al., ). We normalize each of the individual measures and compute their average value.…”
Section: Sample and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we construct composite indices of asymmetric information and uncertainty aggregating the aforementioned proxies (Lin et al., ). We normalize each of the individual measures and compute their average value.…”
Section: Sample and Methodologymentioning
confidence: 99%
“…Our study contributes to the existing literature in several ways. First, we focus on the joint impact of both sides of the double‐sided information problem in M&As, while the prior literature typically considers only one side of the problem, either the target (Reuer, Shenkar, and Ragozzino, ; Officer et al., ) or the bidder (Travlos, ; Moeller et al., ; Lin, Pantzalis, and Park ; Duchin and Schmidt, ). Chemmanur et al.…”
mentioning
confidence: 99%
“…Bartram et al (2013) examine a sample of US firms acquiring foreign targets and conclude that these acquisitions reduce the acquirers' currency risk exposures if they have prior presence in the target's countries. Lin et al (2009) conclude that, because financial derivatives users suffer less information asymmetry than non-users, they tend to have better long-run stock performance than non-users after cross-border M&As.…”
Section: Financial Hedging and Mandasmentioning
confidence: 88%
“…B. Lin, Pantzalis, & Park, 2009). In addition it has been found that derivatives facilitate firms' forecasting by improving the information environment and reducing the information asymmetry resulting in lower agency conflict (Mefteh, Boubaker, & Labégorre, 2012).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 97%
“…Moreover, when considering firms' capital structure the possibility of financial distress and the bankruptcy costs will be higher for firms which have higher levels of debt so such firms are expected to use derivatives to hedge against these risks (Bartram et al, 2009;Jalilvand, 1999;J. B. Lin et al, 2009;Nguyen & Faff, 2002).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%